Discipleship and family ties in Mark and Matthew - Barton, Stephen C. (Society for New Testament Studies monograph series, 1994)
During the first two centuries CE there was a common awareness that familial tensions were generated by conversions to the Christian faith. Yet studies of Christian origins have so far paid little attention to the impact of the Christian movement upon attitudes to family ties and natural kinship. Stephen C. Barton remedies this deficiency by means of a detailed study of the relevant passages in the gospels of Mark and Matthew. First, however, he examines the religious traditions of Judaism and the philosophical traditions of the Greco-Roman world, and shows that the tensions apparent within the Christian movement were by no means unique. In all three areas of thought and religious belief there is found the conviction that familial obligations may be transcended by some higher responsibility, to God, to Christ, or to the demands of philosophy. Mark and Matthew saw the Jesus-movement as offering a transcendent allegiance, which relativised family ties.